Mn-rich SmBaCo0.5Mn1.5O5+δ double perovskite cathode material for SOFCs. (18th October 2019) - Olszewska, Anna; Zhang, Yang; Du, Zhihong; Marzec, Mateusz; Świerczek, Konrad; Zhao, Hailei; Dabrowski, Bogdan
Abstract: SmBaCo0.5 Mn1.5 O5+δ oxide with Sm-Ba cation-ordered perovskite-type structure is synthesized and examined in relation to whole R BaCo0.5 Mn1.5 O5+δ series ( R : selected rare earth elements). Presence of Sm and 3:1 ratio of Mn to Co allows to balance physicochemical properties of the composition, with moderate thermal expansion coefficient value of 18.70(1)·10 −6  K −1 in 300–900 °C range, high concentration of disordered oxygen vacancies in 600–900 °C range (δ = 0.16 at 900 °C), and good transport properties with electrical conductivity reaching 33 S cm −1 at 900 °C in air. Consequently, the compound enables to manufacture catalytically-active cathode, with good electrochemical performance measured for the electrolyte-supported laboratory-scale solid oxide fuel cell with Ni-Gd1.9 Ce0.1 O2-δ |La0.4 Ce0.6 O2-δ |La0.8 Sr0.2 Ga0.8 Mg0.2 O3-δ |SmBaCo0.5 Mn1.5 O5+δ configuration, for which 1060 mW cm −2 power density is observed at 900 °C. Furthermore, the tested symmetrical SmBaCo0.5 Mn1.5 O5+δ |La0.8 Sr0.2 Ga0.8 Mg0.2 O3-δ |SmBaCo0.5 Mn1.5 O5+δ cell delivers 377 mW cm −2 power density at 850 °C, which is a promising result. Highlights: Mn substitution decreases TEC, which is equal 18, 7·10 −6  K −1 for SmBaCo0.5 Mn1.5 O5+δ. Its total conductivity is equal 28 S cm −1 at 600 °C and 33 S cm −1 at 900 °C. SmBaCo0.5 Mn1.5 O5+δ exhibits polarization resistance equal 0.081 Ω cm 2 at 900 °C. Ni-CGO.|LDC|LSGM|SmBaCo0.5 Mn1.5 O5+δ cell delivers 1060 mW cm −2 at 900 °C. Symmetrical SBCM.|LSGM|SBCM cell delivers 377 mW cm −2 at 850 °C.